Differential expression of leukemia inhibitory factor and insulin like growth factor-1 between normal pregnancies, partial hydatidiform moles and complete hydatidiform moles. (September 2018) - Yucel Cicek, Ozge Senem; Hekimoglu, Emine Rumeysa; Turgal, Mert; Atilla, Pergin; Cakar, Ayse Nur; Usubutun, Alp; Beksac, Mehmet Sinan
Abstract: Introduction: Leukemia inhibitory factor (LIF) and insulin like growth factor-1 (IGF-1) are two of the most important growth factors mediating trophoblast actions. We hypothesized that the localization and expression patterns of LIF and IGF-1 in partial and complete hydatidiform moles (HM) compared with normal first trimester placentas may provide an understanding of the proliferative processes in HMs. Methods: The study population included curettage material of women diagnosed as complete or partial HM as a result of histopathological and immunohistochemical examination (complete HM group, n = 8; partial HM group, n = 8) and women undergoing dilatation&curettage for unwanted pregnancies (control group, n = 8). Expression of LIF and IGF-1 among placental cell groups was evaluated immunohistochemically and given a score depending on immunostaining intensity. Results: In normal chorionic villi strong expression of LIF and IGF-1 was present. Both LIF and IGF-1 expressions were weaker in the chorionic villi of complete HMs. In complete mole decidua there was a significant decrease in glandular and endothelial IGF-1 expression along with a decrease in decidual cell LIF expression compared to normal first trimester decidua. LIF expression in extravillous trophoblasts was stronger in complete molar placentas compared to normal placentas. Discussion: LIF and IGF-1 are important regulators of trophoblast proliferation and invasion. Differential expression of LIF and IGF-1 in molar trophoblasts and chorionic villi might have a role in regulation of trophoblasts in complete moles. Decreased expression of glandular IGF-1 and decidual LIF might be related to the decidual changes during trophoblastic proliferation and invasion of decidua in complete HMs. Highlights: LIF staining in decidual cells is weaker in complete moles. Extravillous trophoblasts show strong LIF staining in complete molar pregnancies. Glandular epithelia show weaker IGF-1 expression in complete moles. In normal chorionic villi strong expression of LIF and IGF-1 is present. Both LIF and IGF-1 expressions are weaker in the chorionic villi of complete moles.